(untitled) - Howe, Christopher (London, 1996)
Tells us the development, commercer, and technology in Asia from 1540 to the Pacific war
Keywords: Japan,Nhật Bản,Technology,Công nghệ; Commerce,History,Thương mại,Lịch sử,History,Lịch sử; Japan,Nhật Bản